Оценка параметров фактической зоны при постановке водяных завес в ходе ликвидации последствий чрезвычайной ситуации, связанной с выбросом (проливом) аммиака - Kotov, Геннадий; Eremin, Алексей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
The article offers the results of development and use of semi-empirical model for calculation of actual contamination zone depth, caused by an emergency situation connected with spillage or emission of ammonia. Facts about quantities of the depth actual zone of contamination in depence on the area of the flood and the velocity of wind are given. It also provides the concept of the water curtains efficiency factor and the system of its application for calculation of ammonia concentration change in the surface air after application of water curtains.